Malezya’ da bağımsızlık sonrası din ve devlet: 1957-2016 - Akhmetova, Elmira (Yeni Türkiye Stratejik Araştırma Merkezi, 2017)
This article in Turkish called "Religion and State in Post-Independence Malaysia, 1957-2016" discusses the role of Islam in the state affairs after Malaysian independence.